1.solve for y
2x+4y=12
<u> </u><span><u> -2x -2x</u>
</span><u>4y</u>=<u>12-2x</u>
<u>4 4</u>
y=3-1/2x
step2 plug in y and solve for x
2x+8y=24
2x+8(3-1/2x)= 24
2x+24-4x=24
<u>-2x</u>=<u>0
</u><u>-2 -2</u>
x=0
last step plug in x and solve for y
y=3-1/2x(0)
y=3
Answer: Your answer is 6.772
Step-by-step explanation:
Answer:
y=12.73 x=9
Step-by-step explanation:
Answer:
f(-7) = 268
Step-by-step explanation:
f(x) = 4x^2 – 10x + 2
Let x = -7
f(-7) = 4(-7)^2 – 10(-7) + 2
Exponents first
f(-7) = 4(49) – 10(-7) + 2
Multiply
f(-7) = 196 + 70 + 2
f(-7) = 268